2015
DOI: 10.1002/ppul.23262
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory effects of air pollution on children

Abstract: A substantial proportion of the global burden of disease is directly or indirectly attributable to exposure to air pollution. Exposures occurring during the periods of organogenesis and rapid lung growth during fetal development and early post-natal life are especially damaging. In this State of the Art review, we discuss air toxicants impacting on children's respiratory health, routes of exposure with an emphasis on unique pathways relevant to young children, methods of exposure assessment and their limitatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
109
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(116 citation statements)
references
References 142 publications
(178 reference statements)
2
109
1
4
Order By: Relevance
“…In terms of mortality, both short-term and long-term exposure to air pollution have been linked to mortality from respiratory infections, chronic obstructive pulmonary disease (COPD) and lung cancer [4][5][6][7]. In terms of morbidity, air pollution has been related to asthma attacks, exacerbations of COPD and idiopathic pulmonary fibrosis (IPF) and childhood respiratory infections [4,[7][8][9][10] following short-term exposure, and, albeit with less evidence, to the development of asthma, COPD and lung cancer following long-term exposure [11][12][13][14].…”
Section: Respiratory Effects Of Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of mortality, both short-term and long-term exposure to air pollution have been linked to mortality from respiratory infections, chronic obstructive pulmonary disease (COPD) and lung cancer [4][5][6][7]. In terms of morbidity, air pollution has been related to asthma attacks, exacerbations of COPD and idiopathic pulmonary fibrosis (IPF) and childhood respiratory infections [4,[7][8][9][10] following short-term exposure, and, albeit with less evidence, to the development of asthma, COPD and lung cancer following long-term exposure [11][12][13][14].…”
Section: Respiratory Effects Of Air Pollutionmentioning
confidence: 99%
“…In terms of morbidity, air pollution has been related to asthma attacks, exacerbations of COPD and idiopathic pulmonary fibrosis (IPF) and childhood respiratory infections [4,[7][8][9][10] following short-term exposure, and, albeit with less evidence, to the development of asthma, COPD and lung cancer following long-term exposure [11][12][13][14]. The respiratory disease burden in children due to air pollution is huge, with children dying from respiratory infections in their early years in developing countries [3].…”
Section: Respiratory Effects Of Air Pollutionmentioning
confidence: 99%
“…Evidence has linked air pollutants to a variety of adverse respiratory outcomes in children, from higher rates of bronchitis to an increased incidence of asthma (2). Epidemiologic studies have also shown that air pollution is associated with lung function impairment in children (3)(4)(5)(6).…”
mentioning
confidence: 97%
“…According to the scientific literature, air pollution can affect our health on a global scale and cause many diseases such as cardiovascular diseases, asthma, chronic obstructive pulmonary disease (COPD) and cancer [1][2][3][4][5][6][7][8][9][10][11][12]. The endocrine system has also been studied as a target organ for the harmful effects of air pollutants.…”
Section: Introductionmentioning
confidence: 99%